2021
DOI: 10.15845/voices.v21i2.3308
|View full text |Cite
|
Sign up to set email alerts
|

Music Technology Tools – A Therapist-in-a-box?

Abstract: The purpose of this paper is to contribute to the discussion of technology in music therapy and public health, focusing on the human–computer interaction and the cocreation of mental health. Foundational theory explaining the possible therapeutic dynamics that can occur when engaged in digital technology is presented, along with two case vignettes that illustrate how adolescents interact with digital music technology to promote mental health and wellbeing. The discussion includes reflections concerning actor-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Even though technology is a daily part for many music therapists, there are still many misconceptions about how to implement music technology fluidly in practice (Crooke, 2018;Hahna et al, 2012). Specifically, the use of music technology is experientially, culturally, aesthetically, and relationally very different than using acoustic instruments, and little is known about how these elements impact clinical decision-making in music therapy (Crooke, 2018;Jonassen, 2021;Stensaeth, 2018;Viega, 2018).…”
Section: Digital Music Technologies In Music Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though technology is a daily part for many music therapists, there are still many misconceptions about how to implement music technology fluidly in practice (Crooke, 2018;Hahna et al, 2012). Specifically, the use of music technology is experientially, culturally, aesthetically, and relationally very different than using acoustic instruments, and little is known about how these elements impact clinical decision-making in music therapy (Crooke, 2018;Jonassen, 2021;Stensaeth, 2018;Viega, 2018).…”
Section: Digital Music Technologies In Music Therapymentioning
confidence: 99%
“…Both Stensaeth and Noone (2020) noted that music therapists can develop healthpromoting relationships with music technology. In addition, Jonassen (2021) reported that technology can act as a nonhuman co-agent within a therapeutic relationship, as he focused on the use of iPad as a co-creator. Crooke and McFerran (2019) discussed specific room arrangements, frequency settings, and instrument placement for improvising that does not just offer functionality, but instead showcases the relationship therapists need with various music technologies to best promote health in a way that is individualized and intentional.…”
Section: Subject/object Relationshipmentioning
confidence: 99%
“…In the interview with the therapists, the very act of doing something was highlighted as an important quality of this project. It is not just a "pill" one takes for symptom relief; it is an activity afforded by the technology at hand, a co-agent (Jonassen, 2021), that enables one to co-create one's own improvement. It is something that builds self-efficacy.…”
Section: The Activity Had Value In Itselfmentioning
confidence: 99%
“…2 In the humanistic approach to mental health care, the agents who are involved in the recovery of a patient include both professional therapists and other professions who work together to promote mental health and wellbeing. This approach is presented and discussed in general terms by Bøe and Thomassen (2017), and in terms of technology in music therapy by Jonassen (2021). 3 The recovery perspective grew out of an increased focus on patient involvement.…”
Section: About the Authormentioning
confidence: 99%
“…These devices are relatively inexpensive and are coupled with easy-to-use software. From a music therapist's perspective, these digital systems can act as non-human co-therapists, or "cooperative elements" (Kjetil, 2021).…”
Section: Introductionmentioning
confidence: 99%